2015
DOI: 10.1093/jme/tjv090
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Insecticidal Characteristics of Commercially Available Plant Essential Oils AgainstAedes aegyptiandAnopheles gambiae(Diptera: Culicidae)

Abstract: Aedes aegypti and Anopheles gambiae are two mosquito species that represent significant threats to global public health as vectors of Dengue virus and malaria parasites, respectively. Although mosquito populations have been effectively controlled through the use of synthetic insecticides, the emergence of widespread insecticide-resistance in wild mosquito populations is a strong motivation to explore new insecticidal chemistries. For these studies, Ae. aegypti and An. gambiae were treated with commercially ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 47 publications
3
51
0
Order By: Relevance
“…aegypti were successfully determined in this study in order to later evaluate the synergistic potentials of plant essential oils compared with that of PBO. The LD 50 values obtained in this study for each insecticide were similar to those reported in the literature (Agramonte et al 2017;Norris et al 2015). In general, no insecticide LD 50 differed from values reported in the literature by greater than one order of magnitude.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…aegypti were successfully determined in this study in order to later evaluate the synergistic potentials of plant essential oils compared with that of PBO. The LD 50 values obtained in this study for each insecticide were similar to those reported in the literature (Agramonte et al 2017;Norris et al 2015). In general, no insecticide LD 50 differed from values reported in the literature by greater than one order of magnitude.…”
Section: Discussionsupporting
confidence: 87%
“…The LD 25 and LD 50 values for Ae. aegypti exposed to each insecticide were calculated [ Table 1; permethrin data published previously in Norris et al (2015)]. The most toxic insecticide for Ae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of action behind the toxicity of various plant compounds is complex and diverse. The mechanism of toxic action of various terpenoid compounds include inhibition of acetylcholinesterase, activity at octopamine and tyramine receptors, nicotinic acetylcholine receptor activity, and modulation of GABA-gated chloride receptors in insects [2]. Because of these diverse mechanisms of action and the potential of causing repellency via both antennal perception and fumigant toxicity, resistance to botanical compounds utilized as future repellent technologies may occur more slowly than toward synthetic contact and spatial repellents.…”
Section: Resistance To Repellent Chemistriesmentioning
confidence: 99%
“…The parasites and viruses that are vectored by mosquitoes are responsible for the death of several hundred thousand people each year, with hundreds of millions more infected with debilitating consequences. Moreover, this disease burden is most substantial in developing countries, which lack the infrastructure and economic and educational resources necessary to properly control the spread of mosquito-borne disease [2]. …”
Section: Introductionmentioning
confidence: 99%